E-ART: FRAGMENTATION AND ASSEMBLY - Alessandro Zinna (Texto Digital)
Electronic writing here is analysed through the two conditions set by the Russian linguist Roman Jakobson: in order to be that the electronic language must be able to speak of itself and to create its own aesthetic effects. Inspired by the work of Talan Memmott Self Portrait(s) [as other(s)] metalinguistic and aesthetic traits are read on the background of the evolution of art. From the properties of the plan, the practice, and the value the changes and trends in electronic art are reconstructed. The article concludes by adding a third condition which specifies those set from Jakobson: the untranslatability of aesthetic effects in the languages of art.